The diagnosis, treatment and prevention of gout: The 2014 international clinical guidelines - N. T. Vatutin; Anna Sergeevna Smyrnova; Yu. P. Gritsenko (Современная ревматология, 2015)
The given description of the 2014 new international guidelines prepared by the International Panel of Rheumatologists in the 3e Initiative reflects the diagnosis, treatment and prevention of gout, which are adapted for clinical practice.